The Responsibility of External Auditors in Assessing the Going Concern of Economic Enterprise in Light of Auditing Standard 570 - An Applied Study in Algeria - nedjai, malika; dakhane, mourad (Journal of Research in Finance and Accounting, 2025)
This study examines the role of external auditors in assessing the going concern assumption of Algerian enterprises in accordance with Auditing Standard 570. It evaluates the extent to which Algerian auditors fulfill their responsibilities, particularly their compliance with professional standards, ability to identify indicators of doubt about continuity, and performance of additional audit procedures when events or conditions threaten an entity’s operations. Using a descriptive-analytical method, data from 80 questionnaires completed by Algerian auditors were analyzed using SPSS 27. The results provide more precise insights, showing that 73% of auditors fully apply going-concern assessment procedures, 68% successfully identify risk indicators related to liquidity and solvency issues, and 61% perform extended audit procedures when serious threats to continuity are present. The findings indicate that external auditors’ practices are largely consistent with international auditing requirements and Algeria’s 2016 Auditing Standards (NAA). The study offers practical implications, highlighting the need to reinforce early-warning systems within enterprises and strengthen auditors’ training in financial risk assessment. It also suggests future research avenues on the relationship between audit quality and the effectiveness of going-concern evaluations.